Analysis of restrained composite beams exposed to fire using a hybrid simulation approach. (1st October 2018) - Khan, Mustesin Ali; Jiang, Liming; Cashell, Katherine A.; Usmani, Asif
Highlights: An OpenSees based hybrid simulation approach is used to model composite structures in fire. A 2D frame element model and a 3D shell element model are used for global and local structural behaviour. The detailed shell model is validated against a composite beam test. The Cardington restrained beam test is modelled using hybrid simulation approach with good agreement. The restraint effect to the composite beam is well studied by implementing hybrid simulation. Abstract: Obtaining an accurate simulation of the boundary conditions is very challenging but it is essential in order to represent the true behaviour of the whole structure in fire. In recent years, hybrid simulation has been emerging as an efficient and economical method for simulating realistic boundary conditions in the field of earthquake engineering. This technique can be used to study the load redistribution that may occur in a structural system as a result of locally elevated temperatures. In this paper, the fire-exposed element will be modelled in one analysis (a 3D model) and the rest of the structure in another analysis (a 2D model). This kind of sub-structuring enables the behaviour of the structural system as a whole to be studied. A hybrid simulation (HS) approach is presented and successfully implemented using the OpenFresco and OpenSees software. This approach enables the simulation of the correct restraint provided by the cold structure to the fire affected structural element. The HS analysis of a composite beam is compared with an unrestrained or simply supported version to highlight the difference in behaviour. Finally, the Cardington restrained beam test is modelled to demonstrate the potential of HS technique. Good agreement with the test results highlights that HS approach can be an effective method for studying the behaviour of the whole structural system.